Who persistently consumes dietary supplements? A multifaceted analysis using South Korea’s nationally representative health and nutrition examination survey data - Kwon, Hye-Young (Frontiers in Nutrition, 2023)
Objective: This study aimed to identify multifaceted factors affecting intake of dietary supplements among Koreans. Methods: Korean National Health and Nutrition Examination Survey (KNHANES) data from 2018 to 2020 were obtained, pertaining to functional food intake, health related behaviours and morbidities. A total of 12,031 participants representing the Korean adult population were identified into two groups: 1-year more consumer group (N=4,345) vs. non-consumer group (N=7,686). A logistic regression analysis was performed to analyse the predictors of dietary supplement consumptions. Results: Sociodemographic variables were associated with dietary supplement use. Participants who were female (odds ratio [OR] = 1.85; 95% CI, 1.59-2.15), older (OR = 1.06; 95% CI, 1.04-1.08), married (OR = 6.39; 95% CI, 3.44-11.85), highly educated, and high income earners consumed significantly more dietary supplements. Non-smoking (OR=1.27; 95% CI, 1.06-1.53) and performing aerobic exercise (OR=1.28; 95% CI, 1.13-1.46) predict dietary supplement consumption. Self-rated health status and health-related quality of life increased the likelihood of dietary supplement intake by 1.86 (OR=1.86; 95% CI, 1.04-3.32) and 7.77 times (OR=7.77; 95% CI, 1.66-33.40), respectively. The number of chronic diseases, cancer, or stroke was not significantly associated with intake. Those with obesity tended to less consume dietary supplements (OR=0.85; 95% CI, 0.74-0.97). Hypertension (OR=3.14; 95% CI, 1.36-7.21), osteoporosis (OR=1.47; 95% CI, 1.11-1.95), and asthma (OR=0.44; 95% CI, 0.27-0.73) were significantly associated with the intake. Conclusions: Considering that healthy behaviours and subjective health led to the consumption of dietary supplements, whereas current disease or catastrophic experience did not, the intake of dietary supplements should be included in health promotion in Korea.